The Analysis of Students Reading Interest in Reading English Scientific Article of English Education Students - Ahmad Arafah Assabiq; Sitti Nurjannah; Jusmaniar N; Elihami Elihami (Sublim: Jurnal Pendidikan, 2023)
This research aims to find out how interested in reading scientific articles in English is among students of the English Language Education study program, Faculty of Teacher Training, Education and Literature, Makassar Islamic University. This research is qualitative research using a descriptive analysis approach. The sample taken was 15 students consisting of 5 students in semester 4, 5 students in semester 6, and 5 students in semester 8. The research method used was observation. The instrument used was an interview guide. The collected data is then verified, classified and analyzed, then conclusions are drawn. The results of the research show that interest in reading scientific articles in English for English Language Education study program students is in the High category with a percentage of 78.77 %. The research results were obtained through three main indicators, namely; 1) frequency and quantity of reading (66.83 %); 2) desire to find reading material (81 %); and 3) quantity of reading sources (88.5 %). The inhibiting factors that influence students' interest in reading scientific articles are: 1) Students are still less interested in visiting the campus library because the library's location is not strategic and the availability of scientific articles is very limited; 2) there are still some students who feel burdened by international scientific articles; 3) the average student's English ability is still poor; 4) the internet network facilities provided by the university are very limited; and 5) international scientific article writing training for students is very lacking.